Superoxide anion production and superoxide dismutase and catalase activities in Coxiella burnetii. - Akporiaye, E T (1983)
Coxiella burnetii was examined for superoxide anion (O2-) production and superoxide dismutase and catalase activities. The organism generated O2- at pH 4.5 but not at pH 7.4. The rickettsia displayed superoxide dismutase activity distinguishable from that of the host cell (L-929 mouse fibroblast). Catalase activity was maximal at pH 7.0 and diminished at pH 4.5. These enzymes may account, in part, for the ability of this obligate intracellular parasite to survive within phagocytes.